2010
DOI: 10.1097/ico.0b013e3181a81802
|View full text |Cite
|
Sign up to set email alerts
|

UV-A Collagen Cross-Linking Treatment of Bullous Keratopathy Combined With Corneal Ulcer

Abstract: CXL should be considered as a potential adjuvant therapeutic tool in patients with combined bullous keratopathy and infectious keratitis, who are resistant to traditional topical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 20 publications
2
36
0
8
Order By: Relevance
“…In vitro experiments have supported the view that there is a bactericidal effect of activated riboflavin by using 365-nm UV light [138,139]. When activated by UV light 365-370 nm, riboflavin acts as a photosensitizer in tissues and becomes a generator of reactive oxygen species, creating free radicals to induce new chemical bonds [140][141][142][143][144][145][146]. The aim of treatment with UVA and riboflavin is to create additional chemical bonds inside the cornea in the anterior stroma while minimizing exposure to the surrounding structures of the eye; free radicals generated by this process can cause oxidative damage to DNA and RNA molecules in the surrounding structures [146,147].…”
Section: Antimicrobial Effectmentioning
confidence: 72%
“…In vitro experiments have supported the view that there is a bactericidal effect of activated riboflavin by using 365-nm UV light [138,139]. When activated by UV light 365-370 nm, riboflavin acts as a photosensitizer in tissues and becomes a generator of reactive oxygen species, creating free radicals to induce new chemical bonds [140][141][142][143][144][145][146]. The aim of treatment with UVA and riboflavin is to create additional chemical bonds inside the cornea in the anterior stroma while minimizing exposure to the surrounding structures of the eye; free radicals generated by this process can cause oxidative damage to DNA and RNA molecules in the surrounding structures [146,147].…”
Section: Antimicrobial Effectmentioning
confidence: 72%
“…CXL's antimicrobial and anti-oedematous properties were demonstrated by (Kozobolis et al, 2010) in our report of two patients with combined bullous keratopathy and ulcerative keratitis, resistant to conventional treatments. Former investigators suggested that corneal cross-linking (CXL) might have beneficial impact against corneal melting from bacterial and fungal enzymes, because of the antimicrobial effect of UV-A radiation per se .…”
Section: Corneal Collagen Cross-linking In Complicated Bullous Keratomentioning
confidence: 92%
“…Corneal collagen cross-linking in complicated bullous keratopathy with ulcerative keratitis CXL's antimicrobial and anti-oedematous properties were demonstrated by Kozobolis et al [62] in their report of two patients with combined bullous keratopathy and ulcerative keratitis, resistant to conventional treatments. Both patients presented significant improvement of their vision-threatening corneal ulcer, corneal oedema and BCVA for a follow-up period of 2 months.…”
Section: Corneal Collagen Cross-linking In Infectious Keratitismentioning
confidence: 93%